Conteúdo de proteína do solo relacionada à glomalina em solos do município de Irauçuba-CE e sua relação com a degradação - Silva, Cillas Pollicarto da (2016)
Due to the systematic nature of human activities, combined with the natural actions, the problem of land degradation is increasing more and more and causing a sharp process of desertification, which results in loss of biodiversity, erosion and lack of soil fertility. In view of this, the use of tools indicating the stages of this degradation and recovery is required in order to enable a proper management of these areas. Thus, the study of arbuscular mycorrhizal fungi, such as order to facilitate the recovery of degraded areas, has increased, especially for the production of soil-related protein to Glomalin, which is of great importance for the aggregate stability plus a large potential use as soil quality indicator. Therefore, this study aimed to evaluate soil protein concentrations related to Glomalin, correlating them with the chemical, physical and biological attributes in areas of Irauçuba-EC municipality, namely: area degraded by overgrazing, process area natural regeneration managed by exclusion of domestic animals and native forest characterized by vegetation shrub and tree savanna. They were made collections of deformed soil samples at a depth of 0-10 cm in each area and evaluated attributes of FMA, such as density of total spores, soil protein content related to Glomalin, easily extractable and total (PSRGFE and PSRGT) ; soil chemical properties (pH, Ca2+, Mg2+ Al3+, P, CO, N) and physical (aggregate stability). The results obtained with the average tests showed that among the three areas, only the native forest showed significant differences in the two protein fractions (PSRGFE and PSRGT). However, with respect to the spore density and stability of aggregates, the area of native bush and deletion showed the best average values. Content PSRG associated with other soil attributes, helps to distinguish the quality and monitoring of areas with different levels of soil degradation in Irauçuba-CE. In hierarchical cluster analysis can verify the formation of three groups, confirming the native forest of the distinction with the areas of overgrazing and exclusion, as well as the similarity of these last two areas, indicating that there is a need for more time that there are significant differences between these areas with respect to its recovery.